INVESTIGATING LANGUAGE BELIEFS AND LEARNING EFFECTS: MEDIATING VOCABULARY PERFORMANCE AND MODERATING MULTILINGUALISM PERCEPTIONS AND TEACHER PRACTICES - Mohanad Mohammed Sufyan Ghaleb; Sanjar Mirzaliev (Fonseca, Journal of Communication, 2024)
This study investigates the impact of language beliefs on the learning effect, emphasizing the mediating role of vocabulary learning performance and the moderating influences of perceptions about multilingualism and teacher practices. It aims to deepen the understanding of how cognitive and practical dynamics shape language learning outcomes. A quantitative research design was employed, utilizing data collected from 217 university students enrolled in language programs studying various languages. The research applied validated measurement scales to capture key constructs and analyzed the data using Partial Least Squares Structural Equation Modeling (PLS-SEM) via ADANCO software. The study examined relationships through path analysis and evaluated the mediating and moderating effects of specific variables. The results indicate that language beliefs significantly enhance the learning effect, with vocabulary learning performance acting as a robust mediator. Furthermore, perceptions about multilingualism and teacher practices significantly moderate this relationship, underlining their importance in optimizing learning outcomes. These findings suggest an intricate interplay between student beliefs, instructional practices, and multilingual perceptions in achieving effective language acquisition. This research provides unique insights into the cognitive and contextual factors influencing language learning, offering practical implications for educators and policymakers in designing language programs that foster multilingual competencies and maximize learning outcomes.